Pivaloyl chloride/DMF: a new reagent for conversion of alcohols to chlorides - Dubey, Abhishek; Upadhyay, Arun K.; Kumar, Pradeep (Tetrahedron Letters, 2010)
An efficient procedure for conversion of alcohols into the corresponding chlorides is described. Pivaloyl chloride/DMF complex is employed as a mild and inexpensive reagent. A possible reaction mechanism is proposed. (C) 2009 Elsevier Ltd. All rights reserved.